Stretching effects: High-intensity & moderate-duration vs. low-intensity & long-duration - Freitas, S. R.; Vaz, J. R.; Bruno, P. M.; Andrade, R.; Mil-Homens, P. (International Journal of Sports Medicine, 2016)
This study examined whether a high-intensity, moderate-duration bout of stretching would produce the same acute effects as a low-intensity, long-duration bout of stretching. 17 volunteers performed 2 knee-flexor stretching protocols: a high-intensity stretch (i. e., 100% of maximum tolerable passive torque) with a moderate duration (243.5±69.5-s); and a low-intensity stretch (50% of tolerable passive torque) with a long duration (900-s). Passive torque at a given sub-maximal angle, peak passive torque, maximal range of motion (ROM), and muscle activity were assessed before and after each stretching protocol (at intervals of 1, 30 and 60 min). The maximal ROM and tolerable passive torque increased for all time points following the high-intensity stretching (p<0.05), but not after the low-intensity protocol (p>0.05). 1?min post-stretching, the passive torque decreased in both protocols, but to a greater extent in the low-intensity protocol. 30 min post-test, torque returned to baseline for the low-intensity protocol and had increased above the baseline for the high-intensity stretches. The following can be concluded: 1) High-intensity stretching increases the maximal ROM and peak passive torque compared to low-intensity stretching; 2) low-intensity, long-duration stretching is the best way to acutely decrease passive torque; and 3) high-intensity, moderate-duration stretching increases passive torque above the baseline 30?min after stretching.